Co-producing human and animal experimental subjects: exploring the views of UK COVID-19 vaccine trial participants on animal testing - Vanderslott, S; Palmer, A; Thomas, T; Greenhough, B; Stuart, A; Henry, JA; English, M; Naude, RDW; Patrick-Smith, M; Douglas, N; Moore, M; Hodgson, SH; et al. (SAGE Publications, 2021)
Preclinical (animal) testing and human testing of drugs and vaccines are rarely considered by social scientists side by side. Where this is done, it is typically for theoretically exploring the ethics of the two situations to compare relative treatment. In contrast, we empirically explore how human clinical trial participants understand the role of animal test subjects in vaccine development. Furthermore, social science research has only concentrated on broad public opinion and the views of patients about animal research, whereas we explore the views of a public group particularly implicated in pharmaceutical development: experimental subjects. We surveyed and interviewed COVID-19 vaccine trial participants in Oxford, UK, on their views about taking part in a vaccine trial and the role of animals in trials. We found that trial participants mirrored assumptions about legitimate reasons for animal testing embedded in regulation and provided insight into (i) the nuances of public opinion on animal research; (ii) the co-production of human and animal experimental subjects; (iii) how vaccine and medicine testing, and the motivations and demographics of clinical trial participants, change in an outbreak; and (iv) what public involvement can offer to science.